The falling sky or the collapse of dualities: an analysis of Davi kopenawa’s testimony - Cabel-García, Andrea (2018)
This article is an ethical, academic and theoretical proposal that aims to denaturalize the classic differentiations between the “ones” and the “others” based on a reflection that integrates concepts such as the veil, the second look and the double conscience described by the African-American sociologist W. E. B. Du Bois, together with the concept of the unthinkable by Michel Rolph Trouillot and the reality as a construction by Michael Taussig, in the testimony of Yanomami leader Davi Kopenawa compiled in The Falling Sky (2013) and in the article by anthropologist Jadran Mimica written about the aforementioned testimony. My interest is to demonstrate how Kopenawa’s testimony overturns the classic/traditional model in which indigenous people and whites find themselves trapped in fixed categories, and how critics themselves reject the possibility of reading them in another way.